Awareness of research scholars towards use of e-resources in agriculture - MISHRA, SHUBHAM; SHARMA, F L; VYAS, LATIKA (The Indian Journal of Agricultural Sciences, 2022)
Electronic resources are becoming increasingly popular as a result of their features and benefits. Present study was carried out during 2019 for exploring the awareness of research scholars towards the use of e-resources of selected agriculture universities in Rajasthan. The structured questionnaire method was used to elicit data from the 180 research scholars of three agricultural universities, representing 60 from each of them. The research scholars were classified into four groups: low, average, above average and high based on an arbitrary method of the awareness score obtained by them. The overall distribution of awareness shows that the majority of the research scholars (52.22%) of agriculture universities in Rajasthan belonged to above-average to a high category of awareness followed by 34.44% of them with the average category of awareness and rest 13.34% of them were with low category of awareness. To assess the awareness of research scholars, 25 items related to e-resources were identified. To know the extent of awareness mean percent score (MPS) for each item was calculated, and ranks were assigned. Research scholars awareness regarding mobile apps was 92.40 MPS and ranked first by the respondents. The awareness regarding wikipedia and e-payment was 90.92 and 89.81 MPS and ranked second and third, respectively. Further, found out the difference in awareness among the research scholars towards e-resources in agriculture with the help of ANOVA; the result showed that the calculated F value 0.707 was less than the tabulated value, which is statistically non-significant